If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(1 + -2x) = 12 3x + (1 * 2 + -2x * 2) = 12 3x + (2 + -4x) = 12 Reorder the terms: 2 + 3x + -4x = 12 Combine like terms: 3x + -4x = -1x 2 + -1x = 12 Solving 2 + -1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 12 + -2 -1x = 12 + -2 Combine like terms: 12 + -2 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| -5p+8=14-6p | | 6x^3+42x^2+6x+42= | | 5k-8k=-5k-10 | | 111-6x=10x+13 | | -12(x+6)=3(x+0) | | 48=n-3 | | -1=8-3x | | 1-5n=-4-4n | | M=420(1+3.57) | | 6x+24=10x-10 | | 8+4x=-4+6x | | M=420(1+422.5) | | .50x+.90(30)=.25(128) | | 9y^2-100=0 | | 8a+6a=3a+11 | | 8(x-4)-3(x+1)=2(5-2x) | | 8x+16=112 | | -15-x=6+2x | | -9(x-6)-3=51 | | 4d-3(2d-4)=4-8d+1+d | | 3(x-5)-7(2x-9)=4(x+12) | | 52-2x=7x+15 | | 16(x-1)=-4(x-14) | | r-46=-13 | | 2(4c-1)-1=5c+6 | | -7(x-4)= | | 12+5t=9 | | c+2c+3=3+2(c+2) | | 5x-9=6x+4 | | -3(x+2)-44=1-27 | | 11-2=x | | v=-v+2v |